Complete mitochondrial genome of the freshwater water flea Daphnia magna NIES strain (Cladocera, Daphniidae): Rearrangement of two ribosomal RNA genes. Issue 2 (2nd April 2020) - Lee, Jin-Sol; Kim, Duck-Hyun; Choi, Beom-Soon; Kato, Yasuhiko; Watanabe, Hajime; Lee, Jae-Seong
Abstract: The complete mitochondrial genome was sequenced from the NIES strain of the freshwater water flea Daphnia magna . The sequenced mitochondrial genome size of the NIES strain of D. magna was 17, 432 bp, possessing identical gene order and the contents to those of the congeneric species Daphnia galeata in the genus Daphnia, but 16S and 12S rRNA genes was in opposite direction compared to other daphnid, while ND2 gene was also often found in opposite direction in the genus Daphnia . Overall, the mitochondrial genome of D. magna NIES strain has 13 protein-coding genes (PGCs), two rRNAs, and 22 tRNAs. Of 13 PGCs, four genes ( CO1, CO2, ND5, and ND4 ) had incomplete stop codons. Furthermore, the stop codons of the remaining nine PGCs were TAG and TAA, while the start codons of CO1, ND6, and ND3 genes were ATT, ATT, and ATC, respectively. The base composition of D. magna NIES strain mitogenome shows an anti-G and –T bias (16.5% and 16.0%) on the L strand, respectively.